Magnetic fields with frequency of 217 Hz can reduce cell apoptosis caused by electrochemotherapy. (March 2013) - Mansourian, M.; Firoozabadi, S. Mohammad P.; Shankayi, Z.; Hassan, Z. M.
<x xml:space="preserve">Abstract</x> Nowadays, due to the wide use of mobile phones, extensive studies have been carried out on the effects of magnetic field (MF) on public health. In this paper, we study the effect of 217 Hz MF similar to that generated by GSM900 mobile phones on cancer and healthy cells treated with electric pulse and cytotoxic drug. The experiments conducted include exposure to (a) electric pulses alone (4000 square-wave electric pulses with low amplitude of 70 V/cm and frequency of 5 kHz), (b) electric pulses following MF exposure, (c) electrochemotherapy (electric pulses and cytotoxic drug) alone and (d) MF exposure with subsequent electrochemotherapy. The results indicate that the percentage of apoptosis decreases significantly (p < 0.05) in treatment groups using electrochemotherapy after MF exposure compared to that in treatment groups using electrochemotherapy alone. We observed that 217 Hz MF similar to that generated by GSM900 mobile phones can incur resistance of the cells in response to electric pulses. Our findings implied the existence of amplitude window effect in alternations induced by extremely low-frequency MF.